Spatial and temporal variations of recent shipping along the Northern Sea Route - Li, Xiaoyang; Otsuka, Natsuhiko; Brigham, Lawson W. (Polar Science, 2021)
Spatial and temporal variations of shipping along Russia's Northern Sea Route (NSR) were investigated to better understand the possible drivers of traffic levels and future trends. Daily information for ships sailing along the NSR were collected, and voyage-based analyses were conducted for a period from March 2013 to December 2018. Annual total dead weight tonnage (DWT) increased significantly from 3.95 million tons in 2013 to 24.61 million tons in 2018, and most of this was carried by dry cargo ships, oil tankers and LNG carriers between Europe and the Kara Sea. Annual total DWT was relatively high during 2015–2017 for dry cargo ships, whereas annual total DWT increased rapidly for oil tankers from 2016 and for LNG carriers in 2018. The relatively high level of shipping for dry cargo ships during 2015–2017 is attributable to the Yamal LNG project construction, while the rapidly increased annual total DWT for oil tankers and LNG carriers is due to the transportation of crude oil from the Novy Port project, and LNG from the Yamal LNG project. Recent NSR shipping is mainly driven by development and marine transportation of Russian Arctic natural resources, and this increasing trend should become faster in the near future as operation of the Arctic LNG-2, Taymyr coal and other projects are commissioned. journal article